2023
DOI: 10.1093/scan/nsad008
|View full text |Cite
|
Sign up to set email alerts
|

Are women more empathetic than men? Questionnaire and EEG estimations of sex/gender differences in empathic ability

Abstract: The debate regarding whether women are more empathetic than men has broad scientific, social, and clinical implications. However, previous independent questionnaires and brain imaging studies that tested different samples reported inconsistent results regarding sex/gender differences in empathic ability. We conducted three studies to investigate sex/gender differences in empathic ability using large-sample questionnaire and electroencephalography (EEG) measures. We showed that estimation of empathic ability us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 103 publications
2
6
2
Order By: Relevance
“…This differs from the results obtained in Jordanian and Malaysian studies, where no significant gender differences were observed in willingness to donate 4 16. This trend may be attributed to women’s higher levels of empathy, where questionnaires that measure empathic ability through subjective assessment indicate that women tend to be more empathetic,21 as well as the influence of our sample size, which skewed towards female participants. Men are generally fewer in number, partly because many men travel outside the country to work and/or evade mandatory military service, or are members of the army and thus receive treatment in military hospitals.…”
Section: Discussioncontrasting
confidence: 99%
“…This differs from the results obtained in Jordanian and Malaysian studies, where no significant gender differences were observed in willingness to donate 4 16. This trend may be attributed to women’s higher levels of empathy, where questionnaires that measure empathic ability through subjective assessment indicate that women tend to be more empathetic,21 as well as the influence of our sample size, which skewed towards female participants. Men are generally fewer in number, partly because many men travel outside the country to work and/or evade mandatory military service, or are members of the army and thus receive treatment in military hospitals.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, based on the subjective results, the IRI total score of participants were higher when their partners were absent, and females were more likely to empathize with same gender opponents. Therefore, in same gender dyads, females may better understand each other’s intentions than when competing with unfamiliar opposite gender opponents, which has been confirmed in previous studies ( Pang et al, 2023 ). participants pay more attention to and empathize with same gender competitors, exhibiting higher interbrain synchronization when competing with same gender participants ( Kang et al, 2022 ).…”
Section: Discussionsupporting
confidence: 79%
“…The influence of biological sex on one’s empathetic ability remains an elusive point of ongoing scientific debate [ 25 ]. In our study, significant differences based on sex were observed, with female students and professionals generally reporting greater empathy at baseline.…”
Section: Discussionmentioning
confidence: 99%